Comparative Study of IoT Development Boards in 2021: Choosing right Hardware for IoT Projects - Tewari, Naveen; Deepak, Nitin; Joshi, Mukesh; bhatt, Jai Shankar (2021 2nd International Conference on Intelligent Engineering and Management (ICIEM), 2021)
In today's world our lifestyle has become such, we cannot live without smart devices. These devices are essentially required in our day-to-day routine. They can communicate with themselves as well as with humans by a variety of communication means. With the use of IoT development boards, we can transform these devices into a computerized intelligent system. Various IoT development boards are available with distinct features and costs. It is very hard to find out when to use which development board. This research paper consists of definitions and comparison of various IoT development platforms to make easy for the developer to choose from.